2013
DOI: 10.5301/ejo.5000407
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes with a New Trifocal Intraocular Lens

Abstract: The AT.LISA trifocal IOL provides excellent uncorrected distance, intermediate, and near visual outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
80
5
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 23 publications
26
80
5
11
Order By: Relevance
“…This confirms the ability of the lenses to successfully restore the distance visual function, as also shown for different models of multifocal IOLs [5] [10]- [25]. A mean monocular UDVA of 0.05 ± 0.07 logMAR (decimal 0.89) was reported by Law et al [14] in patients bilaterally implanted with the ATLISA trifocal IOL. Kohnen et al [24] As expected, near visual acuity outcomes improved with increasing near addition of the IOL, with the FineVision IOL showing the best results, followed by ATLISA and Symfony.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This confirms the ability of the lenses to successfully restore the distance visual function, as also shown for different models of multifocal IOLs [5] [10]- [25]. A mean monocular UDVA of 0.05 ± 0.07 logMAR (decimal 0.89) was reported by Law et al [14] in patients bilaterally implanted with the ATLISA trifocal IOL. Kohnen et al [24] As expected, near visual acuity outcomes improved with increasing near addition of the IOL, with the FineVision IOL showing the best results, followed by ATLISA and Symfony.…”
Section: Discussionsupporting
confidence: 81%
“…None of the Symfony patients felt disabled by these symptoms. Law et al [14] found that 80% of patients reported difficulties associated to halo perception at 1 month after implantation of the ATLISA trifocal IOL. This percentage decreased to 40% at 6 months after surgery [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations